PERAN BRAND EQUITY DALAM MEMEDIASI PENGARUH COUNTRY OF ORIGIN IMAGE TERHADAP REPURCHASE INTENTION - Ulfah, Qolbina; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
The purpose of this study was to describe the influence of country of origin image to repurchase intention, the effect of country of origin image of the brand equity, brand equity influence on repurchase intention, and brand equity role in mediating the effects of country of origin image to repurchase intention. The object of this study is that gadgets products Lenovo brand in Denpasar. The number of samples taken as many as 160 people Lenovo brand of gadget users, with non-probability sampling methods, particularly purposive sampling. Data collected through questionnaires. The analysis technique used is the analysis of the path (Path Analysis). Based on the analysis found that the Country of Origin image significantly positive effect on Repurchase Intention, Country of Origin Image significantly positive effect on Brand Equity, Brand Equity significantly positive effect on Repurchase Intention and Brand Equity is able to mediate the effect of Country of Origin Image of the Repurchase intention.
Keywords: repurchase intention, country of origin image, brand equity